The Other Side of Safety : moving from results-based to behavior-based safety - Palmer, Robert (PhD) (Boca Raton: CRC Press, Taylor & Francis, 2023)
"This book presents the alignment of leadership style with personality strengths in expanding a safe leaders' capacity. It helps to influence effectively through the practice of reinforcement, safety performance coaching, exercising empathy, and sustaining healthy relationships. It provides definitions, examples, and applications of the six types of consequences. The text focuses on the behavioral underpinnings for everyday practices in safety like job hazard analysis and safety training. It will serve as an ideal text for students, professionals, and researchers in the fields of ergonomics, human factors, human-computer interaction, and computer engineering"--
Keywords: Industrial safety -- Management; Leadership